Altered protein expression pattern in colon tissue of mice upon supplementation with distinct selenium compounds. Issue 11 (8th June 2017) - Rahn, Jette; Lennicke, Claudia; Kipp, Anna P.; Müller, Andreas S.; Wessjohann, Ludger A.; Lichtenfels, Rudolf; Seliger, Barbara
Abstract : The essential trace element selenium (Se) is controversially discussed concerning its role in health and disease. Its various physiological functions are largely mediated by Se incorporation in the catalytic center of selenoproteins. In order to gain insights into the impact of Se deficiency and of supplementation with different Se compounds (selenite, selenate, selenomethionine) at defined concentrations (recommended, 150 μg/kg diet; excessive, 750 μg/kg diet) in murine colon tissues, a 20‐week feeding experiment was performed followed by analysis of the protein expression pattern of colon tissue specimens by 2D‐DIGE and MALDI‐TOF MS. Using this approach, 24 protein spots were identified to be significantly regulated by the different Se compounds. These included the antioxidant enzyme peroxiredoxin‐5 (PRDX5), proteins with binding capabilities, such as cofilin‐1 (COF1), calmodulin, and annexin A2 (ANXA2), and proteins involved in catalytic processes, such as 6‐phosphogluconate dehydrogenase (6PGD). Furthermore, the Se compounds demonstrated a differential impact on the expression of the identified proteins. Selected target structures were validated by qPCR and Western blot which mainly confirmed the proteomic profiling data. Thus, novel Se‐regulated proteins in colon tissues have been identified, which expand our understanding of the physiologic role of Se in colon tissue.